The Existence of Javanese Benthik as a Traditional Sports Game in the Midst of Modern Disruption (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this research is to study and analyze traditional Javanese benthic games amidst digital modernization. This is because playing plays an important role in the emotional, cognitive and physical development of children. The writing method used is literature study to find answers to problematic questions using document databases, social reality from relevant sources such as social media and the results of previous research. The results and discussion of this study provide an illustration if the experience gained while playing games gives children the ability to find solutions to the problems they face in a social environment. Games, which are the main entertainment objects, have moved from a social environment to a virtual environment as a result of technological developments. Furthermore, it was found that online games which are mostly played by children have a number of unfavorable impacts without regulation, and the irony is that traditional sports games such as Javanese benthik are no longer known. Digital games tend to contain elements of violence which are mostly played by children. However, it is different from traditional games, the specific benefits obtained are training skills and preserving culture because with the development of the era, traditional games have begun to be forgotten. Therefore, the concern of all parties is needed to maintain their existence, because children have a role as the next generation of the nation, they need to model behavior, social maturation, and self-esteem